The Development of Self-Help Book as A Media in Career Planning for Undergraduate Student in Indonesia - Dzinnun Hadi (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
This research aims to develop a self-help book to inform the students about the steps in career planning. This research uses The Research and Development method developed by Borg and Gall. The research was classified as a small scale R & D research because the research was carried out using only a few steps. The steps are research and collect information, planning, development of the initial product format, initial product validation, and product revisions. In the validation step the product is assessed by three expert validators, the media expert validator, the material expert validator, and also assessed by the user's validator, the students in SMAN 1 Tulungagung. This research produces a self-help book entitled “Kamu Mau Jadi Apa?”. The contents of the self-help book in career planning are Know Yourself: Who You Are; Find Out the Talent; Recognize the Interest; My Dream Goals; My Future, Specify the Goals, Recognize the Personal Values; Continue Studying to the College Successfully; Join the Work World Successfully. The percentage of book feasibility results from each validator is, the media expert validator is 92,5% (very feasible), the material expert validator is 70,83% (feasible), and the user validator or the students is 86,41 (very feasible). The conclusion of this research is this book is categorized as very feasible with an average percentage of 82%. It is hoped that this self-help book about career planning can be applied effectively, and also hopefully this research can be applied in other schools